Anosognosia predicts default mode network hypometabolism and clinical progression to dementia. (13th March 2018) - Therriault, Joseph; Ng, Kok Pin; Pascoal, Tharick A.; Mathotaarachchi, Sulantha; Kang, Min Su; Struyfs, Hanne; Shin, Monica; Benedet, Andrea L.; Walpola, Ishan C.; Nair, Vasavan; Gauthier, Serge; Rosa-Neto, Pedro
Abstract : Objective: To identify the pathophysiologic mechanisms and clinical significance of anosognosia for cognitive decline in mild cognitive impairment. Methods: We stratified 468 patients with amnestic mild cognitive impairment into intact and impaired awareness groups, determined by the discrepancy between the patient and the informant score on the Everyday Cognition questionnaire. Voxel-based linear regression models evaluated the associations between self-awareness status and baseline β-amyloid load, measured by [ 18 F]florbetapir, and the relationships between awareness status and regional brain glucose metabolism measured by [ 18 F]fluorodeoxyglucose at baseline and at 24-month follow-up. Multivariate logistic regression tested the association of awareness status with conversion from amnestic mild cognitive impairment to dementia. Results: We found that participants with impaired awareness had lower [ 18 F]fluorodeoxyglucose uptake and increased [ 18 F]florbetapir uptake in the posterior cingulate cortex at baseline. In addition, impaired awareness in mild cognitive impairment predicted [ 18 F]fluorodeoxyglucose hypometabolism in the posterior cingulate cortex, left basal forebrain, bilateral medial temporal lobes, and right lateral temporal lobe over 24 months. Furthermore, participants with impaired awareness had a nearly 3-fold increase in likelihood of conversion to dementia within a 2-year time frame. Conclusions: Our results suggest that anosognosia is linked to Alzheimer disease pathophysiology in vulnerable structures, and predicts subsequent hypometabolism in the default mode network, accompanied by an increased risk of progression to dementia. This highlights the importance of assessing awareness of cognitive decline in the clinical evaluation and management of individuals with amnestic mild cognitive impairment.